2003
DOI: 10.1051/0004-6361:20030485
|View full text |Cite
|
Sign up to set email alerts
|

The embedded star clusters in the nebulae vdB-RN 92 and Gy 3–7 in Canis Majoris R1

Abstract: Abstract. We employed J, H and K s photometry from the 2MASS Point Source Catalogue to study the embedded star clusters in the nebulae vdB-RN 92 and Gy 3-7, which are located in the molecular cloud Canis Majoris R1. We employed colourcolour and colour-magnitudes diagrams together with theoretical pre-main sequence isochrones to derive their fundamental parameters. Ages are based on the fraction of stars with anomalous colours, supposedly of types Herbig AeBe and T Tauri. The vdB-RN 92 cluster has an age of 5-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Five resolved CMaX sources belong to these clusters, for which we have obtained similar ages. For the older cluster VdB-RN92 (5-7 Myr, Soares & Bica 2003) we have identified four other CMaX sources, but only one of them (CMaX-68) has compatible age, while the others seem to be massive stars for which the age determination is uncertain. Figure 10 presents the results, in the form of two panels, showing the broad distributions of ages and masses for all the CMaX sources in Field 1 and Field 2 respectively.…”
Section: Stellar Masses and Agesmentioning
confidence: 85%
“…Five resolved CMaX sources belong to these clusters, for which we have obtained similar ages. For the older cluster VdB-RN92 (5-7 Myr, Soares & Bica 2003) we have identified four other CMaX sources, but only one of them (CMaX-68) has compatible age, while the others seem to be massive stars for which the age determination is uncertain. Figure 10 presents the results, in the form of two panels, showing the broad distributions of ages and masses for all the CMaX sources in Field 1 and Field 2 respectively.…”
Section: Stellar Masses and Agesmentioning
confidence: 85%
“…Undoubtedly, vdB 92 is part of a star-forming complex that deserves further analyses. With an approach that differs in various aspects from the present one, Soares & Bica (2003) studied the brighter sequences of vdB 92, deriving an age of 5-7 Myr, a mean visible absorption A v = 4.4, and d ≈ 1.5 kpc.…”
Section: Previous Data On Cr 197 and Vdb 92mentioning
confidence: 99%
“…Later, Sugitani et al (1995) observed a small bright-rimmed core, BRC 27, along the L1657 cloud edge and found infrared (IR)-excess stars there, and subsequently Ogura et al (2002) found 32 Hα emission stars towards the same cloud core. Soares & Bica (2002, 2003 used the 2MASS catalogue to study four small clusterings of young stars, including BRC 27. Gregorio-Hetem et al (2009) and Fernandes et al (2015) used X-ray data from ROSAT to identify young stars across a ∼5 sq.…”
Section: Introductionmentioning
confidence: 99%